PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN IPA BERBASIS PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA - Alin, Awalina Barokah; Kurnia, Ira Restu; Kalsum, Umi (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2023)
This study aims to determine the influence of the use of problem based learning science media on the scientific literacy skills. This study used pseudo-experimental research with a nonequivalent comparison-group design. The sample of this study was class IV A of 30 students who were treated with problem based learning science media and V B class which totaled 32 students with no treatment using problem based learning science media. Data collection was carried out with a test of scientific literacy skills that had been tested for validity and reliability. Data analysis using Univariate Analysis of Variance with 5% of significance level. The results showed that the difference in the average score of the pre-test was 65.50 while the average post-test score of interest in learning was 84.00. Problem based learning science media has a significant and positive effect on the scientific literacy skills seen from the calculation of 5,076 and P of 0.000; P=0.000<0.05;